2013
DOI: 10.1515/bmc-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Alternative genetic code for amino acids and transfer RNA revisited

Abstract: Abstract:The genetic code is highly conserved among all organisms and its evolution is thought to be strictly limited. However, an increasing number of studies have reported non-standard codes in prokaryotic and eukaryotic genomes. Most of these deviations from the standard code are attributable to tRNA changes relating to, for example, codon/anticodon base pairing and tRNA/ aminoacyl-tRNA synthetase recognition. In this review, we focus on tRNA, a key molecule in the translation of the genetic code, and summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Recent studies have identified a number of non-canonical tRNA species that were previously mis-annotated or undetected due to their unusual recognition elements, anticodon sequences and irregular secondary structures (615). Interestingly, although the function of many of them remains unknown (5,6,8), some of these non-canonical tRNAs are known to be responsible for changes to the universal meaning of the genetic code (7,1015). Therefore, proper identification of tRNA genes is important to identify genetic code variations in nature (10,13).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified a number of non-canonical tRNA species that were previously mis-annotated or undetected due to their unusual recognition elements, anticodon sequences and irregular secondary structures (615). Interestingly, although the function of many of them remains unknown (5,6,8), some of these non-canonical tRNAs are known to be responsible for changes to the universal meaning of the genetic code (7,1015). Therefore, proper identification of tRNA genes is important to identify genetic code variations in nature (10,13).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified nematode-specific novel tRNA genes, designated nev-tRNAs, e.g., nev-tRNA Gly (CCC) and nev-tRNA Ile (UAU), which contain 15–20-nt V-arm structures and are solely charged with Leu instead of Gly or Ile in vitro [ 8 , 16 ]. To obtain further evidence of the functionality of nev-tRNAs in cells, the following two characteristics were analyzed: (1) their maturation, with the addition of 3′ CCA; and (2) their subcellular localization.…”
Section: Resultsmentioning
confidence: 99%
“…This faithful translation of the genetic code is a central pillar of molecular biology, and is maintained by the accuracy of tRNA aminoacylation and codon–anticodon matching. Therefore, any deviation from these sequential molecular recognition rules reflects the imperfection of the translation process, resulting in ‘genetic code ambiguity’ [ 6 8 ]. A number of instances of natural codon reassignment suggest that genetic code ambiguity has evolutionary implications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations